Analysing firm performance in Chinese IT industry: DEA Malmquist productivity measure. (6th June 2011) - Chen, Xiaohong; Wang, Xiaoding; Wu, Desheng Dash; Zhang, Zejing
Chinese IT industry has become more important and maturity after development for tens of years and come up quickly in global IT market. They may have huge influence on Chinese IT market or even the world. This paper is concerned with the study on exploring the performance of Chinese IT industry, including the managerial, technical and scale efficiencies and their changes over time. We employ data envelopment analysis (DEA)-based Malmquist method to measure the performance of listed IT firms in China, in the period of 2005 to 2007 and reveal the detailed technology and efficiency changes over time by analysing decomposed components of Malmquist index. Furthermore, the technical diffusion of Chinese IT industry is tested by efficiency convergence analysis. Accordingly, the IT companies can make decisions on the functions and strategies shifts that are beneficial to the performance improvement and achieving competitive advantages.